Lincoln's Trident : The West Gulf Blockading Squadron during the Civil War - Browning, Robert M. Jr., 1955- (Book collections on Project MUSE., 2015)
In Lincoln's Trident, Coast Guard historian Robert M. Browning Jr. continues his magisterial series about the Union's naval blockade of the Confederacy during the American Civil War. Established by the Navy Department in 1862, the West Gulf Blockading Squadron operated from St. Andrews Bay (Panama City), Florida to the Rio Grande River. As with the Navy's blockade squadrons operating in the Atlantic, the mission of the West Gulf Blockading Squadron was to cripple the South's economy by halting imports and disrupting cotton exports, the South's main source of hard currency. The bloc.